Real wage rigidities and the cost of disinflations: A comment on Blanchard and Galí - Guido Ascari; Christian Merkl (Kiel Institute for the World Economy (IfW), 2007)
This paper analyzes the cost of disinflation under real wage rigidities in a micro-founded New Keynesian model. Unlike Blanchard and Galí (2007) who carried out a similar analysis in a linearized framework, we take non- linearities into account. We show that the results change dramatically, both qualitatively and quantitatively, for the steady states and for the dynamic adjustment paths. In particular, a disinflation implies a prolonged slump without any need for real wage rigidities.
Keywords: E52; E31; 330; Sticky Prices; Real Rigidities; Disinflation; Reallohn; Lohnrigidität; Arbeitslosigkeit; Geldpolitisches Ziel; Ungleichgewichtstheorie; New-Keynesian Phillips Curve